1998
DOI: 10.1128/aem.64.12.4676-4682.1998
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity among Isolates of Vibrio vulnificus Recovered from Eels ( Anguilla anguilla ) in Denmark

Abstract: The findings of this study demonstrate that Vibrio vulnificus isolates recovered from diseased eels in Denmark are heterogeneous as shown by O serovars, capsule types, ribotyping, phage typing, and plasmid profiling. The study includes 85 V. vulnificus isolates isolated from the gills, intestinal contents, mucus, spleen, and kidneys of eels during five disease outbreaks on two Danish eel farms from 1995 to 1997, along with a collection of 12V. vulnificus reference strains. The results showed that more than one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…Moreover, nonmotile V. vulnificus isolates and the strain CECT 5198 (biotype 2, serovar A) displayed O-antigenic cross-reactivity, as they all gave a positive reaction with antisera obtained against isolate S3-I2-36 and strain CECT 5198 respectively, but only after cell-suspensions were boiled at 115 1C for 2 h (Table 2). Thus, the overall features of our V. vulnificus isolates clearly indicated that they are eel-pathogenic (biotype 2) strains, in accord with reports by other authors Hi et al, 1999;Fouz & Amaro, 2003;Fouz et al, 2006). Until now, such V. vulnificus biotype 2 serovar A strains had only been recovered from diseased individuals obtained from intensive eel farms, but never from wild eel samples (Fouz & Amaro, 2003;Fouz et al, 2006).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, nonmotile V. vulnificus isolates and the strain CECT 5198 (biotype 2, serovar A) displayed O-antigenic cross-reactivity, as they all gave a positive reaction with antisera obtained against isolate S3-I2-36 and strain CECT 5198 respectively, but only after cell-suspensions were boiled at 115 1C for 2 h (Table 2). Thus, the overall features of our V. vulnificus isolates clearly indicated that they are eel-pathogenic (biotype 2) strains, in accord with reports by other authors Hi et al, 1999;Fouz & Amaro, 2003;Fouz et al, 2006). Until now, such V. vulnificus biotype 2 serovar A strains had only been recovered from diseased individuals obtained from intensive eel farms, but never from wild eel samples (Fouz & Amaro, 2003;Fouz et al, 2006).…”
Section: Resultssupporting
confidence: 90%
“…In contrast, the bacterium has been scarcely isolated in Europe from oysters, clams, mussels, as well as from sediment and plankton in aquatic ecosystems (Hi et al, 1998;Arias et al, 1999;Maugeri et al, 2004). Most European V. vulnificus isolates have been recovered from diseased eels cultured in brackish and freshwater farms (Biosca et al, 1991;Hi et al, 1999;Fouz & Amaro, 2003;Fouz et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The eel pathogen Vibrio vulnificus biotype 2 causes an emergent disease similar to the classical vibriosis (Song et al ., 1990; Biosca, 1994; Austin and Austin, 1999). This biotype is subdivided into four different serovars (Biosca et al ., 1996a; 1997a; Høi et al ., 1998b; Fouz and Amaro, 2003), serovar E being epidemiologically the most important one. Thus, serovar E causes epizootics and outbreaks in farmed eels (Biosca, 1994; Amaro and Biosca, 1996; Biosca et al ., 1997a; Tison et al ., 1982) as well as sporadic cases of severe septicaemia in humans (Veenstra et al ., 1993; Amaro and Biosca, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Biotype 3 was discovered in Israel to refer to a group of atypical isolates of the species from human infections related with tilapia manipulations . Thus, strains of V. vulnificus of biotype 2 had the unique ability to infect eels and the disease was reported in different European eel farms (Høi et al 1998a;Dalsgaard et al 1999).…”
Section: Introductionmentioning
confidence: 99%